Validation of tensile strength of notched hybrid polymer composite using Whitney-Nusimer point stress model. (2020) - Rajkumar, K.; Ramraji, K.; Manojkumar, M.; Gnanavelbabu, A.
Abstract: In recent years, a few research attempts were made on the feasibility of hybridization using selected natural and synthetic fibers which provide good structural properties. Most of the structural assembling operations, the fiber reinforced plastic laminates were used which involve several riveted joints. This requires the presence of various sizes of hole and eventually a zone of stress concentration. This leads to a tensile strength analysis study by the effect of various sizes of open-hole made on the laminate composites. This is a crucial step in defining their suitability in applications. In the present work, investigation on mechanical properties of a hybrid combination of natural fibers human hair-coconut coir and synthetic glass fiber-laminate has been carried out. Eight sets of tensile and impact specimens were prepared with centrally drilled various sizes of hole and experimentally tensile and impact strength were recorded. Additionally, Whitney Nusimer point stress model was used to validate the experimental values. The stress distribution around the centre hole was studied by the Finite Element Method (FEM). An increase in hole diameter found to increases hole sensitivity. The finite element analysis indicated a much higher stress concentration region along the tensile loading direction.